Examining the Effect of Earplugs, Eye Mask, and Earplugs + Eye Mask on the Sleep Quality in Intensive Care Patients: a Randomised Controlled Trial - Aysun Kazak Saltı; Hasret Topalı; Erdoğan Yolbaş; Sevilay Hintistan (Türk Uyku Tıbbı Dergisi)
Objective: Quality sleep, which plays an important role in the physical, cognitive, immunological, and psychosocial functions of patients, is imperative, especially for patients hospitalised in intensive care units (ICU) to recover from their critical illnesses. The aim of this study was to investigate the effect of earplugs (EP) and eye mask (EM) on sleep quality in ICU patients. Materials and Methods: The sample of the study consisted of 120 patients hospitalised in the general ICU of Siirt State Hospital between July 2021-May 2022. Patients were divided into four groups as EP, EM, EP + EM and control group. Each patient in the related group wore EP, EM, and EP in combination with EM between 22:00-06:00 and was allowed to sleep in this way. Data were collected using the “patient description form” and "Richards Campbell Sleep Questionnaire (RCSQ)". Results: According to that the dependent samples t-test performed for intra-group comparison, there was a statistically significant increase between pretest and post-test RCSQ mean scores of the patients in the EP, EM, and EP + EM groups (tEP=7,899, tEM=17,268, tEP + EM=9,381, p<0.001); whereas, there was no significant difference between pretest and post-test RCSQ mean scores of the patients in the control group (tC=1,084, p>0.05). Also, the first three factors that negatively affected the sleep quality of ICU patients were noise (71.6%), light (60.8%) and nursing interventions (49.1%). Conclusion: The application of EM only was found to be the most effective nursing practice in enhancing the sleep quality of patients hospitalised in the ICU.